Effect of brain endurance training on fatigue and physical endurance among stroke survivors: a non-blinded randomized controlled trial - Jayasree Sai L; Prathap Suganthirababu; Dhanusia S; Harika Valluri (Faculty of Medicine, Universitas Trisakti, 2026)
BackgroundPost-stroke fatigue (PSF) is a multifactorial impairment characterized by persistent tiredness not relieved by rest, and affects nearly half of stroke survivors, leading to poor physical endurance which limits recovery and overall quality of life. Limited evidence suggests that combining cognitive and physical training might help in reducing fatigue. Brain endurance training (BET) involves both cognitive training and physical training, targeting PSF. The study aimed to evaluate the effect of BET on fatigue and physical endurance among stroke survivors. MethodsA parallel group pilot randomized controlled trial was carried out in a private setting with 30 stroke survivors. Patients were randomized into two groups. Group A (n=15) received BET and group B (n=15) received conventional physiotherapy. Both groups underwent training for 65 minutes per day, thrice a week for eight weeks. Primary outcomes were Fatigue Severity Scale (FSS) and Six-Minute Walk Test (6MWT). Statistical analysis was performed using the chi-square test and independent t-test. ResultsAt baseline, no significant differences were observed between groups for FSS and 6MWT (p>0.05). The BET group reported better reduction in fatigue (FSS: 5.39 ± 0.18 to 3.48 ± 0.16, p<0.001) and improvement in physical endurance (6MWT: 202.03 ± 4.35 to 273.35 ± 6.26, p<0.001) than the control group (FSS: 5.25 ± 0.10 to 4.19 ± 0.06) (6MWT: 200.53 ± 2.72 to 222.70 ± 3.64). ConclusionBrain endurance training is a feasible and safe approach for reducing fatigue and improving physical endurance among stroke survivors.